How do the electricity market and carbon market interact and achieve integrated development?--A bibliometric-based review. (15th February 2023) - Li, Yan; Feng, Tian-tian; Liu, Li-li; Zhang, Meng-xi
Abstract: The global climate and environment are deteriorating. Countries have accelerated the development of the carbon market. The interaction and integration research between electricity market and carbon market helps to better reduce carbon emissions. To understand the knowledge domains and evolution of carbon–electricity markets, we downloaded 54, 739 related articles from the Web of Science Core Collection between 1991 and 2022 based on the themes of the "electricity market" and "carbon market". CiteSpace visual software was used to perform cooperative analysis, keyword co-occurrence analysis and cocited analysis. Based on the visual analysis results, we further conducted qualitative analysis of hot research directions and analyzed the development direction of the coupling relationship. We found that there exists mechanism correlations, price interactions, transaction information interactions and transaction behavior interactions, which have an impact on low-carbon investment decisions, power structure optimization and carbon emission reduction. In the future, the development of a low-carbon economy and the integration of renewable energy into the grid will lead to more frequent electricity–carbon markets interactions. Graphical abstract: Image 1 Highlights: Visual analysis of the interactive and integration development of electricity-carbon market. Conduct qualitative analysis of hot research directions. Conclude the development direction of the coupling relationship.